Tiku, Kabupaten Agam Menggunakan Metode MNDWI dan Citra Landsat 8 Oli - Suci Ramayana; Fajrin Fajrin; Ilham Armi; Defwaldi Defwaldi (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
Tiku Beach in Tanjung Mutiara District, Agam Regency, West Sumatra is a 12.77 km coastal area experiencing continuous shoreline changes due to abrasion and accretion. This study aims to identify and map shoreline changes and calculate the area of abrasion and accretion in 2014, 2019, and 2024 using the Modified Normalized Difference Water Index (MNDWI) method based on Landsat 8 OLI satellite imagery. The MNDWI method utilizes the reflectance difference in the Green band (Band 3) and SWIR band (Band 6) to automatically separate the land-water boundary. Shoreline change analysis was performed using Net Shoreline Movement (NSM) and End Point Rate (EPR) methods through ArcGIS 10.8 software with the Digital Shoreline Analysis System (DSAS) extension. Analysis of 336 transects shows that accretion is more dominant than abrasion along Tiku Beach. The largest accretion was recorded at transect 230 with an NSM value of 71.3 m and an EPR rate of 7.12 m/year, while extreme abrasion occurred at transect 249 with an NSM value of -121.67 m and an EPR rate of -12.15 m/year. The evolution of the shoreline shows that in 2014 the coastline was still relatively stable, then in 2019 mild abrasion occurred in the west along with accretion in the east, and by 2024 this pattern became more pronounced. The results of this study are expected to serve as a scientific basis for decision-making in coastal disaster mitigation planning and sustainable coastal management in Agam Regency.